Instagram and Students’ Creativity in Writing: A Students Voice - Lazuwardiyyah, Fairuz; Khasanah, Siti Uswatun; Safriyani, Rizka (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2019)
This paper is intended to discuss the students’ voice about the use of Instagram picture and video to develop students’ creativity in writing. The participants involved in this study were 25 students of the English Teacher Education Department at the State Islamic University of Sunan Ampel Surabaya.  This descriptive quantitative studies distributed questionnaires in the online mode. The finding of this study showed that most of the students had a positive response to the development of creativity in writing. There were 76% of students believe that picture and video could encourage students creativity in generating ideas, especially in writing.